Ecoprint as an Environmentally Based Art Learning Innovation at SDN Sukamanah, Mangunjaya Village - Septiana, Fajar Indra; Permana, Angga Prayoga; Nursajjiddah, Hanna; Intan, Rosmayanti; Azzahra, Salma (CV. Rayyan Dwi Bharata, 2025)
Ecoprint is a technique for dyeing fabric and/or batik using natural materials. Ecoprint techniques are introduced to elementary school students because at that age children can train their motor skills independently and are able to think creatively. The purpose of the ecoprint introduction activity is to provide knowledge about ecoprint and skills for students in utilizing natural materials or plants around the school. The methods used are lectures, demonstrations, practices and evaluations. Evaluation uses direct direction and direct observation of Ecoprint products that have been made by students. Students have been able to print motifs and colors from leaves and flowers on fabrics producing Ecoprint products according to their respective creativity, even the results of this Ecoprint can be displayed or sold.